The Effectiveness of Canva-Based Digital Books to Improve Civics Learning Outcomes of Grade V Students of SD Negeri 055981 Beruam - Br Simanungkalit, Priska Nurlia; Saragi, Daulat; Lubis, Wildansyah (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to test the effectiveness of Canva-based digital books to improve the civics learning outcomes of fifth grade students at SD Negeri 055981 Beruam. This research is the research and development of the 4D model (Define, Design, Develop, and Disseminate) conducted at SD Negeri 055981 Beruam with research subjects consisting of material, media, language, teachers, and 30 students. data collected from validation questionnaires of material, language, and media experts to determine the level of feasibility, then teacher and student questionnaires to determine the level of practicality, and tests to determine the level of effectiveness. The results showed that the results of the material expert assessment were 92.5% very feasible achievement, then the media expert was 91.7% very feasible achievement, and the language expert was 90% very feasible achievement. Calculated from the assessment of the three experts, an average of 91.7% was very feasible achievement. Then the results of the practicality test conducted by teachers and students obtained an average student assessment of 87.75% very practical achievement and an average teacher assessment of 93.75% very practical achievement, so that calculated from the practicality assessment, an average of 90.75% very practical achievement was obtained. Finally, the effectiveness of canva-based digital books is assessed by the gain test, and a value of 0.56 is obtained in the medium category. So it can be concluded that the canva-based digital book developed has a level of feasibility, practicality, and effectiveness that can be used to improve student learning outcomes.